PELAKSANAAN PEMBERIAN KREDIT USAHA RAKYAT (KUR) MIKRO PADA PT.BANK RAKYAT INDONESIA (BRI) UNIT TUANKU TAMBUSAI PEKANBARU - Syafrianto '; Firdaus '; Maryati Bachtiar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Micro Business Loan (KUR) Micro is a credit or working capital financing aimed at business actors who do not have additional collateral, but in the implementation the dealer still requested additional collateral to the prospective customer.The purpose of writing this thesis, namely: first, to know the implementation process of Micro Business Loans (KUR) at PT. Bank Rakyat Indonesia (BRI) Unit Tuanku Tambusai Pekanbaru. Second, knowing the reason of PT. Bank Rakyat Indonesia (BRI) Unit Tuanku Tambusai Pekanbaru requested additional collateral to prospective customers in Micro Small Business Credit (KUR) process. The type of this research is sociological research, that is research obtained directly from society.From the results of the study there are several things that can be concluded that the reason for requesting additional collateral to prospective customers is to guarantee and provide a sense of security to the bank against the funds it provides and to ensure that the debtor has the intention and good faith to fulfill his achievements because his securities serve as additional collateral. The author's suggestion, the dealer to further improve the quality of service and remove additional collateral requests so as to provide a legal certainty for the community.Keyword: Implementation - Micro KUR - Additional Collateral